On occurrence of vitrophyres in Macaronesia - Mitchell-Thomé, R. C. (1982)
Vitrophyres, defined as rocks in which more than 50% of the groundmass is glass, irrespective of composition and whether porphyritic or not, occur in Macaronesia. In the literature, vitreous rocks are ofter referred to, but where chemical analyses are lacking and only inadequate petrographic descriptions are given, it is not always clear what proportion of such may actually be vitrophyres. On the other hand, references are given to vitrophyres in the region. Vitrophyres certainly are present in the Azores, Canaries and Cape Verde archipelagoes, but are more doubtful in Madeira and the Selvagens. In Tenerife, these rocks are most voluminous though more widespread in Gran Canaria. In the former, the Teide-Viejo volcano complex comprises essentially obsidian-type rocks. It appears that the Macaronesian vitrophyres are of Quaternary/Sub-Recent age, though those of Gran Canaria and La Palma belong to Middle-Lower Miocene. As not all islands have been given the same petrological attention, it is possible that further investigations would show vitrophyres to be more abundant than at present known.